Post-translational regulation and gene repression mechanisms of Arabidopsis HD-Zip IV transcription factors - Ahmad, Bilal (My University, 2025)
Class IV homeodomain leucine-zipper (HD-Zip IV) transcription factors (TFs) drive epidermal differentiation and cell fate determination in plants. These proteins contain a conserved domain architecture comprising a DNA-binding (DB) homeodomain (HD), zipper loop zipper (ZLZ) dimerization domain, steroidogenic acute regulatory (StAR) protein-related lipid transfer (START) domain, and START-adjacent domain (STAD). Despite decades of research, their post-translational regulatory mechanisms remain unexplored. The studies herein focused on the nuclear import and transcriptional repression mechanisms of HD-Zip IV proteins. Arabidopsis thaliana members GLABRA2 (GL2) and PROTODERMAL FACTOR2 (PDF2) served as models to elucidate the nuclear localization mechanisms of HD-Zip IV TFs. GL2 contains a monopartite nuclear localization sequence (NLS) overlaps with HD. Mutational analyses showed that the NLS is essential for PDF2 and GL2 nuclear localization, while EYFP-NLS live imaging confirmed its sufficiency. Genetic dissection provided evidence that DNA binding and nuclear localization are separable functions despite the partial overlap between the NLS and HD. Protein-protein interaction (PPI) analyses confirmed NLS-dependent interactions between GL2 and importin alpha (IMPa) isoforms. In accordance with this, IMPa triple mutants (impa-1,2,3) exhibited defects in EYFP:GL2 nuclear localization and trichome development. The gene repression mechanisms of HD-Zip IV TFs were dissected by studying GL2 and two other HD-Zip IV members, Arabidopsis thaliana MERISTEM L1 LAYER (ATML1) and HOMEODOMAIN GLABROUS11 (HDG11). GL2 possesses two ethylene-responsive element-binding factor-associated amphiphilic repression (EAR) motifs, comprising an LxLxL pattern on the amino (N)- and carboxy (C)-termini. Mutations in the N-terminal EAR motif (gl2[superscript EARN]) resulted in partial functional defects. In contrast, C-terminal mutations led to complete loss-of-function, likely due to protein misfolding. A modified EAR motif, SUPERMAN REPRESSIVE DOMAIN X (SRDX) fusion to gl2[superscript EARN], rescued epidermal defects. PPI analysis using yeast two-hybrid (Y2H) and co-immunoprecipitation (Co-IP) revealed EAR-motif-dependent interactions between GL2 and the TOPLESS (TPL) and TPL-RELATED corepressor proteins. Future experiments, such as RNA sequencing and TPL/TPR mutant analyses, will further elucidate GL2 transcriptional targets and repression mechanisms. Unlike GL2, ATML1 and HDG11 lack an identifiable repressive domain and interact with a small EAR-motif-containing adaptor protein, GL2 INTERACTING REPRESSOR 1 (GIR1), to orchestrate their transcriptional target expression and cell fate determination. A gir1 T-DNA insertion mutant displayed giant cell overproduction in the sepals, similar to ATML1 overexpression. PPI via Y2H and Co-IP revealed that the GIR1 C-terminal cysteine residues are required for the interaction with ATML1 and HDG11 STAD, whereas the N-terminal EAR motif is critical for the interaction with TPL and TPR. Co-IP experiments also showed that GIR1 acts as an adapter to link ATML1 with TPL/TPR corepressors. Genetic complementation experiments demonstrated that wild-type GIR1, but not EAR or cysteine mutants, can rescue the gir1 mutant phenotype, highlighting the importance of EAR and cysteine motifs for GIR1 function in planta. Collectively, these findings suggest a model in which GIR1 recruits TPL/TPR to ATML1 and HDG11 target loci for balanced regulation of gene expression to orchestrate epidermal cell fate. Overall, these studies have mechanistically uncovered the nuclear localization and gene regulatory mechanisms of Arabidopsis HD-Zip IV TFs in fine-tuning transcriptional target expression for proper epidermal development. Given that the epidermis is the first line of defense and HD-Zip IV orthologs are present in major agronomical crops, these findings can be broadly applied to guide molecular toolkits to improve yield and resilience to environmental stresses.
Keywords: Arabidopsis; HDG11; HD-Zip IV; Gene repression; GLABRA2; GIR1; ATML1; Nuclear localization; Protein-protein interactions